Abnormal adaptation over time of motor network recruitment in multiple sclerosis patients with fatigue. (August 2016) - Rocca, Maria A; Meani, Alessandro; Riccitelli, Gianna C; Colombo, Bruno; Rodegher, Mariaemma; Falini, Andrea; Comi, Giancarlo; Filippi, Massimo
Objectives: Using functional magnetic resonance imaging (fMRI) during a motor task, we investigated the functional correlates of central fatigue in multiple sclerosis (MS), and adaptation of motor network recruitment during a prolonged effort. Methods: Motor fMRI was obtained from 79 MS patients (50 fatigued (F), 29 non-fatigued (nF)) and 26 matched healthy controls (HC). Cognitive and physical fatigue were rated using the Modified Fatigue Impact Scale (MFIS). Results: Compared to HC and nF patients, F-MS patients experienced reduced activations of the left middle temporal gyrus, left supplementary motor area (SMA), bilateral superior frontal gyrus, left postcentral gyrus and basal ganglia regions. They also showed increased activation of the right middle frontal gyrus (MFG). Time-modulation analysis showed a reduced activity of the SMA and right precentral gyrus, and increased activity of the basal ganglia in HC. Such a trend was impaired in F-MS patients. In MS patients, increased MFG activity was related to MFIS scores. Physical MFIS score was related to a reduced recruitment of the right thalamus and SMA. Conclusions: Abnormalities and impaired timing of activation between different areas of the motor and executive networks occur in F-MS patients. The dysfunction of critical cortical areas contributes to the occurrence of central fatigue.